Thermal system for a new flexible composite tank - Liu, Yuxi; Li, Qian; Zhu, Haoyu (Frontiers in Materials, 2022)
A flexible thermal insulation system is proposed in this study considering the application and promotion of flexible composite materials in the field of marine engineering. This system aims to provide a cost-effective and convenient thermal insulation solution for avoiding impurity precipitation and waxing plug caused by extremely low temperature during the mining, transportation, and storage of oil. It mainly includes two parts: the insulation layer and the heating source. In accordance with the laws of thermodynamics and the main characteristics of the flexible structure, two sets of different insulation systems are designed, and the model tests are performed to compare their performance in terms of heating efficiency, thermal insulation performance, and temperature field distribution under the same environmental conditions. Compared with the plan one thermal insulation system, the plan two thermal insulation system has lower requirements for heating power. The temperature field distribution inside the flexible structure is more uniform, and the difference between the highest point temperature and the lowest point temperature is only 7.18 °C.